STUDY OF DISPARATE SECTORS IN FISHERIES - RAJE, S. G.; SINGH, V. V.; SHARMA, ARPITA (Journal of Indian Fisheries Association, 2015)
Fisheries employ a number of people and fisheries industry is truly anamalgamation of various disparate sectors. Fisheries play an important rolein Indian economy and it provides employment to a number of people. Forplanning of integrated development of fisheries industry and resourcemanagement, a considerable amount of information is required. In this papera study of the disparate sectors with regards to the nature of work, numberof workers, sex-wise participation, earning type and earning in Indian Rupeesin the year 1991-92, 1992-93, 1993-94 and 1999-2000 has been done in a selectedfishing village. The geographical locale where the study has been done isVersova fishing village which is a major fish landing centre in Mumbai. Thestudy has revealed that there are a number of disparate sectors in fisheriesand in thsi fishing village on an average, a boat owner provided employmentto 30.60 people in the year 1994 and to 19.25 people in 1999. Though thisnumber has shown a decreasing trend with the advancement of years, it ishowever, seen that a number of people are employed in various disparatesectors in fisheries. It is necessary to highlight this and in any developmentalplanning, all these sectors should be given equal importance.Keywords :Disparate sectors, Fisheries, Employment